PERSEPSI BADAN OTONOM PELAJAR ISLAM INDONESIA (BO PII) WATI SUMSEL TERHADAP BERITA CROSSHIJABERS CNNINDONESIA.COM - Syarifah Adawiyah; Aliasan Aliasan; Ahmad Harun Yahya (Tabayyun: Journal of Journalism, 2020)
This thesis is the result of research describing how the perception of Badan Otonom Pelajar Islam Indonesia (BO PII) Wati on crosshijabers news on Cnnindonesia.com. The presence of crosshijabers or men dressed in syar'i is considered unsettling because it can gives a bad stigma for Muslim women. Therefore, researchers are interested in raising the title "Perception of the Badan Otonom Pelajar Islam Indonesia (BO PII) Wati Sumsel Against Crosshijabers news at Cnnindonesia.com" as research material. This research aims to answer the question of how the perception of the Badan Otonom Pelajar Islam Indonesia (BO PII) Wati of crosshijabers news on Cnnindonesia.com and the factors that influence it. The research methodology used is a qualitative approach. Data collection was carried out by direct interviews with informants in this study, namely the management of Badan Otonom Pelajar Islam Indonesia (BO PII) Wati Sumsel. The results showed that the administrators of the Badan Otonom Pelajar Islam Indonesia (BO PII) Wati Sumsel had two forms of response that emerged, there are positive and negative responses. Factors that influence the perception of Badan Otonom Pelajar Islam Indonesia (BO PII) Wati on crosshijabers news on Cnnindonesia.com include the attention stage, and also the interpretation which includes the use of news, the level of news reading satisfaction, and also experience. The following are suggestions that the author proposes: For people who are media users to be wiser in receiving news. For the media, depth is needed in following up this phenomenon completely so that this phenomenon does not occur again. Keywords: Perception, Indonesian Badan Otonom Pelajar Islam Indonesia (BO PII) Wati, News, Crosshijabers,